The Critical Strips of the Sums 1+2𝑧+⋯+𝑛𝑧 - G. Mora; J. M. Sepulcre (Abstract and Applied Analysis)
We give a partition of the critical strip, associated with each partial sum 1+2𝑧+⋯+𝑛𝑧 of the Riemann zeta function for Re 𝑧<−1, formed by infinitely many rectangles for which a formula allows us to count the number of its zeros inside each of them with an error, at most, of two zeros. A generalization of this formula is also given to a large class of almost-periodic functions with bounded spectrum.